SFRP1 variations influence susceptibility and immune response to Mycobacterium tuberculosis in a Chinese Han population - Zhao, Zhenzhen; Peng, Wu; Hu, Xuejiao; Zhang, Jingya; Shang, Mengqiao; Zhou, Juan; Zhou, Yi; Song, Xingbo; Lu, Xiaojun; Ying, Binwu; Chen, Xuerong (Infection, genetics and evolution, 2016)
SFRP1 acts as a well-established inhibitory regulator of the Wnt signaling pathway, whose polymorphisms have been demonstrated to be associated with the risk of inflammation, infection as well as cancer. We verified the hypothesis that single nucleotide polymorphisms (SNPs) within SFRP1 gene are associated with susceptibility and clinical characteristics of tuberculosis disease in a Chinese Han population. Six candidate SNPs were genotyped using MassARRAY method in a case–control design (260 tuberculosis patients and 252 healthy controls). A comprehensive analysis of single locus including the genotypic, allelic frequencies and the genetic models, haplotypic construction as well as gene–gene interaction was conducted to investigate the relationships between SNPs and TB. Significant SNPs were further interrogated in relation to TB clinical features and host inflammatory status. Genotype frequencies of rs4736958 and rs7832767 within SFRP1 gene were significantly different (p=0.011, p=0.008, respectively) between tuberculosis group and control group. Subjects carrying C allele for rs4736958 showed a decreased tuberculosis risk (OR=0.66, 95% CI=0.51–0.87, p=0.003), whereas individuals carrying rs7832767 T allele had a significant increased risk in tuberculosis susceptibility (OR=1.32, 95% CI=1.01–1.74, p=0.046). Genetic model analysis revealed that dominant, co-dominant and recessive models of rs4736958 were associated with decreased susceptibility to tuberculosis (p all <0.05), while the recessive and co-dominant models of rs7832767 were related to significantly increased risk for tuberculosis (p all <0.05). There was a reduced tuberculosis risk in association with the haplotype CC (representing rs3242 and rs4736958) of SFRP1 (OR=0.73, 95% CI=0.56–0.96, p=0.026). Further stratification analysis indicated that TB patients with genotype CT for rs4736958 were associated with higher CRP concentrations, and heterozygous patients (CT genotype) of rs7832767 trended towards greater ESR levels. SNPs rs4736958 and rs7832767 of SFRP1 gene were significantly associated with tuberculosis susceptibility and might influence the expression levels of inflammatory markers of tuberculosis patients in a Chinese Han population. •Our observation suggested that rs7832767 may be a hopeful susceptible locus for TB infection in China.•This is the first report of rs4736958 association with TB risk in Chinese Han population.•Rs7832767 and rs4736958 were correlated with the expression levels of CRP and ESR.